Basic Psychological Needs and Psychological Well-Being Among Undergraduate Students in China: The Mediating Role of Autonomous Motivation and Academic Engagement - Li Y; Sueb R; Said Hashim K (Psychology Research and Behavior Management)
Yan Li,1,2 Rosilawati Sueb,2 Khadijah Said Hashim2 1School of Language and Cultures, Youjiang Medical University for Nationalities, Baise, Guangxi, 533000 People’s Republic of China; 2Faculty of Education, Universiti Teknologi MARA, UITM Puncak Alam Campus, Puncak Alam, Selangor, 42300 MalaysiaCorrespondence: Rosilawati Sueb, Faculty of Education, Universiti Teknologi MARA, UITM Puncak Alam Campus, Puncak Alam, Selangor, 42300, Malaysia, Tel +60133631205, Email rosil334@uitm.edu.myPurpose: From the perspective of positive psychology, and based on Self-Determination Theory and Sustainable Happiness Theory, this study explores the relationship between basic psychological needs and psychological well-being among undergraduate students, as well as the mediating roles of autonomous motivation and academic engagement.Methods: A survey was conducted among 439 undergraduate students using the Basic Psychological Needs Scale, Learning Motivation Scale, Academic Engagement Scale, and Psychological Well-being Scale.Results: Basic psychological needs were significantly and positively correlated with undergraduate students’ psychological well-being. Academic engagement partially mediated the relationship between basic psychological needs and psychological well-being. However, autonomous motivation did not mediate this relationship. Furthermore, autonomous motivation and academic engagement served as chain mediators in the relationship between basic psychological needs and psychological well-being.Conclusion: Basic psychological needs are not only directly related to undergraduate students’ psychological well-being but are also indirectly associated with their psychological well-being through the mediating role of academic engagement and the chain mediating role of autonomous motivation and academic engagement.Keywords: Basic Psychological Needs, Psychological Well-being, Autonomous Motivation, Academic Engagement, Undergraduate Students